Development of Solar PV Powered Smart Flood Monitoring System Apply for the Unmanned Substation - Jumali, Muhamad Nizaruddin (Progress in Engineering Application and Technology, 2023)
Flood has always been a disaster to the world. Sudden flood and flash flood is unpredictable and can cause much damage. The unmanned substation also gets the impact of a flood unpredictably occurs. Many components and equipment will be damaged and will cost loss for the community. The person in charge must be notified if a flood will occur, as any device can warn them when it occurs. The existing water level device is inconvenient because of the device design, just like a giant ruler with a number on it. There are no components to send the data to the person in charge about the condition of the water level. Because of this, the development of a Solar PV Powered Smart Flood Monitoring System Applied for the Unmanned Substation is made. This project is developed to measure water level and define the weather condition, whether rain or not. Then the project was developed to send the data through the IoT platform and notify the user about the weather and water levels. This project is developed using an ESP32 module as the microprocessor, a water level sensor as the weather condition definer, and an ultrasonic sensor as the water level measurer. The IoT platform used is the Blynk interface, which can show the sensor data reading and give notifications through the smartphone.